Comparative genomic analysis of the WRKY III gene family in populus, grape, arabidopsis and rice. Issue 1 (December 2015) - Wang, Yiyi; Feng, Lin; Zhu, Yuxin; Li, Yuan; Yan, Hanwei; Xiang, Yan
Abstract Background WRKY III genes have significant functions in regulating plant development and resistance. In plant, WRKY gene family has been studied in many species, however, there still lack a comprehensive analysis of WRKY III genes in the woody plant species poplar, three representative lineages of flowering plant species are incorporated in most analyses:Arabidopsis (a model plant for annual herbaceous dicots), grape (one model plant for perennial dicots) andOryza sativa (a model plant for monocots). Results In this study, we identified 10, 6, 13 and 28 WRKY III genes in the genomes ofPopulus trichocarpa, grape (Vitis vinifera ), Arabidopsis thaliana and rice (Oryza sativa ), respectively. Phylogenetic analysis revealed that the WRKY III proteins could be divided into four clades. By microsynteny analysis, we found that the duplicated regions were more conserved between poplar and grape thanArabidopsis or rice. We dated their duplications by Ks analysis ofPopulus WRKY III genes and demonstrated that all the blocks were formed after the divergence of monocots and dicots. Strong purifying selection has played a key role in the maintenance of WRKY III genes inPopulus . Tissue expression analysis of the WRKY III genes inPopulus revealed that five were most highly expressed in the xylem. We also performed quantitative real-time reverse transcription PCR analysis of WRKY III genes inPopulus treated with salicylic acid, abscisic acid and polyethylene glycol to explore their stress-related expression patterns. Conclusions This study highlighted the duplication and diversification of the WRKY III gene family inPopulus and provided a comprehensive analysis of this gene family in thePopulus genome. Our results indicated that the majority of WRKY III genes ofPopulus was expanded by large-scale gene duplication. The expression pattern ofPtrWRKYIII gene identified that these genes play important roles in the xylem during poplar growth and development, and may play crucial role in defense to drought stress. Our results presented here may aid in the selection of appropriate candidate genes for further characterization of their biological functions in poplar. Reviewers This article was reviewed by Prof Dandekar and Dr Andrade-Navarro.